Subtypes of sport-related concussion: a systematic review and meta-cluster analysis - Langdon, S.; Königs, M.; Adang, E. A. M. C.; Goedhart, E.; Oosterlaan, J. (Sports Medicine, 2020)
Objective: Current clinical guidelines provide a unitary approach to manage sport-related concussion (SRC), while heterogeneity in the presentation of symptoms suggests that subtypes of SRC may exist. We systematically reviewed the available evidence on SRC subtypes and associated clinical outcomes. Data Sources: Ovid Medline, Embase, PsycINFO, and SPORTDiscus Eligibility Criteria for Selecting Studies: Electronic databases were searched for studies: (i) identifying SRC symptom clusters using classification methodology; or (ii) associating symptom clusters to clinical outcome variables. A total of 6,146 unique studies were identified, of which 75 full texts were independently assessed by two authors for eligibility. A total of 22 articles were included for systematic review. Data Extraction: Two independent authors performed data extraction and risk of bias analysis using the Cochrane Collaboration tool. Data Synthesis: Six studies found evidence for existence of SRC symptom clusters. Combining the available literature through Multiple Correspondence Analysis (MCA) provided evidence for the existence of a migraine cluster, a cognitive-emotional cluster, a sleep-emotional cluster, a neurological cluster, and an undefined feelings cluster. Nineteen studies found meaningful associations between SRC symptom clusters and clinical outcomes. Clusters mapping to the migraine cluster were most frequently reported in the literature and were most strongly related to aspects of clinical outcome. Conclusions: The available literature provides evidence for the existence of at least five subtypes in SRC symptomatology, with clear relevance to clinical outcome. Systematically embedding the differentiation of SRC subtypes into prognosis, clinical management, and intervention strategies may optimize the recovery from SRC.